ANALISIS SERTA PERENCANAAN OUTPUT DAN KESEMPATAN KERJA DI PROVINSI SUMATERA BARAT - Martilova, Novera; Aimon, Hasdi; Syofyan, efrizal (Jurnal Kajian Ekonomi, 2013)
This article focused on analyze (1) Effect of investment, consumption, government expenditure and employment to the output in West Sumatera. (2) The influence of investment, wages, inflation, and output on the employment in west Sumatera (3). Prospect of output and employment in West Sumatera 2013-2020. Data used time series of (I year kuartal 2001 – IV year kuartal 2010). This article use analyzer model equation of simultaneous with method of Two Stage Least Squared (TSLS). The result of research concludes that (1) The investment have a significant and positive impact on the output, consumption have significant and positive impact on the output, government expenditure have significantly and positive on the output and employment have a significant and positive impact on the output in West Sumatera. (2) Investment, inflation, and output significantly influence the employment in West Sumatera. While the wages is significant and negative effect on employment in West Sumatera. (3) Prospect of output and employment in West Sumatera 2013-2020 is positive. Keywords: Output, Employment, Investment, Consumption, Government expenditur, Wages, and Inflation.